Organic Carbon Aging During Across‐Shelf Transport - Rui Bao; Masao Uchida; Meixun Zhao; Negar Haghipour; Daniel Montlucon; Ann McNichol; Lukas Wacker; John M. Hayes; Timothy I. Eglinton (Geophysical Research Letters)
Abstract Compound‐specific radiocarbon analysis was performed on different grain‐size fractions of surficial sediments to examine and compare lateral transport times (LTTs) of organic carbon. 14C aging of long‐chain leaf wax fatty acids along two dispersal pathways of fluvially derived material on adjacent continental margins implies LTTs over distances of ~30 to 500 km that range from hundreds to thousands of years. The magnitude of aging differs among grain size fractions. Our finding suggests that LTTs vary both temporally and spatially as a function of the specific properties of different continental shelf settings. Observations suggest that 14C aging is widespread during lateral transport over continental shelves, with hydrodynamic particle sorting inducing age variations among organic components residing in different grain sizes. Consideration of these phenomena is of importance for understanding carbon cycle processes and interpretation on sedimentary records on continental margins.